Impact of Fermented Corn–Soybean Meal on Gene Expression of Immunity in the Blood, Level of Secretory Immunoglobulin A, and Mucosa-Associated Bacterial Community in the Intestine of Grower–Finisher Pigs - Lu, Junfeng; Zhu, Mengqing; Cao, Haigang; Zhang, Xuan; Wang, Zhaolu; Zhang, Xiaoyu; Li, Xiao; Hu, Jianhong; Yang, Gongshe; Shi, Xin'e (Frontiers in Veterinary Science, 2020)
This study was conducted to determine the effect of a fermented corn-soybean meal (fermented feed, [FF]) on the gene expression of immunity in the blood, level of secretory immunoglobulin A (sIgA), and mucosa-associated bacterial community in the colon of grower-finisher pigs. In this study, crossbred barrows (Duroc × Landrace × Large White) were randomly assigned to either an unfermented corn-soybean diet (Ctrl) (n = 6) or an FF diet (n = 6) and then examined the expression of immunity using real-time reverse transcription polymerase-chain reaction in the blood, sIgA using enzyme-linked immunosorbent assay (ELISA), and changes in the bacterial community using Illumina Hiseq sequencing in the mucosa of the duodenum and colon. Compared with control pigs fed a standard diet, the results showed that FF caused upregulation of the mRNA expression of Toll-like receptor 3 (TLR3), TLR4, TLR6 and TLR8 in the blood (P < 0.05). Moreover, sequencing of 16S rRNA genes in duodenal mucosa samples indicated that the FF diet had a lower proportion of Tenericutes (P < 0.05) in the duodenal mucosa-associated microbiota and FF significantly increased the percentage of Rikenellaceae and Christensenellaceae but decreased the abundance of Lachnospiraceae (P < 0.05) in the colonic mucosa-associated microbiota. The ELISA results showed that FF significantly increased the concentration of sIgA in the colonic mucosa (P < 0.05). More importantly, our correlation analysis indicated that the gene expression of immunity in the blood and concentration of sIgA was associated with colonic mucosa-associated microbiota. Our data provide new knowledge into the adaptation response of the intestine to FF feeding in monogastric animals.